Extraction, purification, and characterization of polysaccharides from Alhagi pseudoalhagi with antioxidant and hypoglycemic activities. (October 2022) - Mutailifu, Paiheerding; Nuerxiati, Rehebati; Lu, Chunfang; Huojiaaihemaiti, Haibaier; Abuduwaili, Aytursun; Yili, Abulimiti
Abstract: Alhagi pseudalhagi is a well-known herbal remedy in traditional medicine. The current study aims to isolate and characterize the polysaccharides of A. pseudalhagi, as well as assess their antioxidative and hypoglycemic effects in vitro. Using DEAE-52 and Sephadex G-100 chromatographic columns, obtained one neutral (APs-1) and two acidic (APs-2, APs-3) polysaccharides. HPGPC, GC–MS, UV, FT–IR, Congo red, CD, and SEM analyses were used to characterize their physicochemical properties. The major monosaccharides in APs-1 and APs-2 were rhamnose, mannose, glucose and galactose, while in APs-3 was only rhamnose and galactose. They were heteropolysaccharides with average molecular weights of 57.8 kDa, 630 kDa, and 707 kDa, respectively. All three polysaccharides were in α-glycosidic linkage and had a triple-helical conformation with varying degrees of asymmetry. APs-1and APs-2 exhibited relatively loose, curly, honeycomb-like texture, whereas APs-3 was cross-linked filamentous with a smooth surface. In vitro, all three polysaccharides demonstrated remarkable antioxidant effects on the DPPH and ABTS radicals, with, APs-3 demonstrating excellent α-glucosidase inhibiting capacity of the three polysaccharides. showed better ABTS scavenging and α-glucosidase inhibiting capacity compared to APs-1 and APs-2. These findings suggest that A. pseudalhagi polysaccharides have the potential to act as an antioxidant and a hypoglycemic agent. Graphical Abstract: ga1 Highlights: Three heteropolysaccharides were obtained from the aerial parts of Alhagi pseudalhagi . The polysaccharides possessed various molecular weights and monosaccharides compositions. The polysaccharides have triple-helix structure, and different morphological properties. All three polysaccharides exhibited desirable antioxidant and hypoglycemic activities in vitro. This study provides structural characterization to the future use of Alhagi polysaccharides.